2022
DOI: 10.1039/d1sc06782f
|View full text |Cite
|
Sign up to set email alerts
|

Stability matters, too – the thermodynamics of amyloid fibril formation

Abstract: Amyloid fibrils are supramolecular homopolymers of proteins that play important roles in biological function and disease. These objects have received an exponential increase in attention during the last decades, due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 139 publications
0
51
0
Order By: Relevance
“…It is also known that partially stable structures are many times involved in aggregation and in nucleation of amyloid fibrils formation. ,, Once initiated and formed, the aggregation process may persist for a long period of time given its unique kinetic stability. On the other hand, amino acid mutations, associated with aggregation growth, increase the population of partially unfolded and misfolded states by decreasing stability and cooperativity of the native state. The thermodynamic stability is important to prevent promiscuous interactions . Following these arguments, it is possible that one of the reasons for the elimination of the aggregation process of Top7-2F5-biotin is the loss of the intermediate and partially folded state in the thermodynamic F ( Q ) profile upon biotinylation.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that partially stable structures are many times involved in aggregation and in nucleation of amyloid fibrils formation. ,, Once initiated and formed, the aggregation process may persist for a long period of time given its unique kinetic stability. On the other hand, amino acid mutations, associated with aggregation growth, increase the population of partially unfolded and misfolded states by decreasing stability and cooperativity of the native state. The thermodynamic stability is important to prevent promiscuous interactions . Following these arguments, it is possible that one of the reasons for the elimination of the aggregation process of Top7-2F5-biotin is the loss of the intermediate and partially folded state in the thermodynamic F ( Q ) profile upon biotinylation.…”
Section: Resultsmentioning
confidence: 99%
“…The process of amyloid fibril formation is reversible, although the equilibrium monomer concentration is small for many proteins [ 48 ]. This concentration equals the thermodynamic equilibrium constant of fibril dissociation K F if only one form of the monomer is present and participates in aggregation.…”
Section: Kinetics and Thermodynamics Of Amyloid Fibril Formationmentioning
confidence: 99%
“…Amyloids have since been recognized as a pathological conformation accessible to diverse proteins in many human diseases, including Alzheimer’s (AD) and Parkinson’s diseases [ 6 , 7 , 8 ]. However, several landmark experiments demonstrated that the amyloid state is not restricted to proteins involved in pathological conditions but can also be accessible to virtually any protein under the appropriate experimental conditions [ 6 , 8 , 9 , 10 , 11 , 12 ]. The resulting fibrils can in some cases lead to a novel pathological condition [ 13 ].…”
Section: The Amyloid Statementioning
confidence: 99%